2015
DOI: 10.1021/acscatal.5b01446
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide: A Convenient Metal-Free Carbocatalyst for Facilitating Aerobic Oxidation of 5-Hydroxymethylfurfural into 2, 5-Diformylfuran

Abstract: By thermal treatment in vacuum, graphite oxide prepared from Hummers' method was exfoliated and partially reduced. This procedure imparts the graphene oxide (GO) the high reactivity with 2,2,6,6-tetramethyl-piperidin-1-oxyl (TEMPO) as co-catalyst for selective oxidation of 5-hydroxymethylfrufural (HMF) to 2, 5-diformylfuran (DFF) under certain conditions (100% HMF conversion with HMF selectivity 99.6% at 80 wt.% GO loading, 1 atm air pressure). This study found that GO could function as an oxidant for anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 51 publications
2
107
2
Order By: Relevance
“…The I D /I G values of NOC‐m are in the range of 0.83∼0.88, suggesting that their defects density is close to each other . ESR spectra (Figure S7) showed a broad peak attributable to the unpaired spins at the edges of graphitic carbon network ,…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The I D /I G values of NOC‐m are in the range of 0.83∼0.88, suggesting that their defects density is close to each other . ESR spectra (Figure S7) showed a broad peak attributable to the unpaired spins at the edges of graphitic carbon network ,…”
Section: Resultsmentioning
confidence: 85%
“…Various factors affect the catalytic performance of carbons, such as the surface area, chemical composition (e. g. N, P or B substitution), defects (e. g. zig‐zag and armchair edges), and surface groups (e. g. oxygen groups) ,,,. Correlation of the structural information and the activities of the carbons above suggest that the surface area, N content and defects are not the determining parameters for the activity (Table and Figure S21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] One of the most attractive directions in biorefinery developmenti sd evotedt ot he production of furan derivatives, such as furfural and 5-hydroxymethylfurfural (HMF). [7,8] HMF,w hich is ap roduct of C6-based carbohydrates,i s widely considered as av ersatilep latform chemical for the productiono fabroad range of fine chemicals, [9] pharmaceuticals, [10] and liquid transportation fuels. [10][11][12] Selective oxidation of HMFi so ne of the most essential transformations in the biorefinery.…”
Section: Introductionmentioning
confidence: 99%
“…MIL-101 has been widely used in the oxidation of hydrocarbons, such as cyclohexene,i ndane, and dibenzothiophene. [31] In addition, it was reported that the acids formed by the thermolysis of DMSO may act as catalysts in the oxidation of HMF. [31] In addition, it was reported that the acids formed by the thermolysis of DMSO may act as catalysts in the oxidation of HMF.…”
mentioning
confidence: 99%